Pengaruh Media Numerik Digital Terhadap Kemampuan Konsep Bilangan - melia eka daryati melia (Institut Agama Islam Negeri Madura, 2023)
Practical learning media is often done using books, markers, magazines, and blackboards in introducing the concept of numbers. Even though early childhood requires sensorimotor activity that is symbolic in understanding new experiences and training children's concentration. The study aimed to determine differences in number concept abilities using digital numeric media in group B1 at Kindergarten Negeri 6 Bengkulu South. The total sampling of respondents in class B1 amounted to 10 with an age range of 5-6 years. The research method uses a quantitative approach with a pre-experimental research type using a one-group pretest - posttest research design. Data collection techniques using observation and tests. The data obtained were analyzed using the Independent Sample T-test. The results showed that Asymp.Sig (2-tailed) has a value of 0.000 <0.05, so H0 is rejected and Ha is accepted, meaning that there is an average difference between the pretest and posttest so that it can be concluded that the number concept ability of children aged 5-6 years is influenced by the media digital numeric.